PENGEMBANGAN MODUL BLENDED LEARNING PADA MATERI RADIASI ELEKTROMAGNETIK BERBASIS GOOGLE CLASSROOM DALAM PEMBELAJARAN FISIKA DI SMA - Zhuha Moeslimah; Zulirfan Zulirfan; Yennita Yennita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Absract: Blended learning module is a module whose application can be done in two learning: face to face learning and also on online learning. The purpose of this research is to design and produce a valid blended learning module on electromagnetic radiation material as a source of learning physics in class XII in high school and this research uses Google Classroom as a learning management system. This research is expected to be used to facilitate teachers to apply blended learning as well as alternative learning. Research of development module used is research with the ADDIE model. This research is limited to the development stage that has been done validation of module because the researcher does not examine the effectiveness of learning activities in the class with the modules developed. The results of the study gave the conclution that the blended learning module developed on the electromagnetic radiation material for class XII are valid and can be used in learning to support the teaching and learning process so to be better.Keywords: Module, Blended Learning, Electromagnetic Radiation, and Google Classroom